THE EFFECTIVENESS OF PHYSICS LEARNING FROM HOME CLASS X STUDENTS DURING THE CORONA VIRUS TIME - Michaela Crystina Falensia Gerans; Melyanus B. U. Kaleka; Maimunah H. Daud (Program Studi Pendidikan IPA FKIP Universitas Jember, 2022)
This study aims to determine the effectiveness of learning physics from the homes of class X students during the corona virus period. This type of research uses survey research using a qualitative descriptive approach. The subjects in this study were physics subject teachers, totaling 1 person and all students of class X science at SMA Muhammadiyah totaling 20 people. Data collection techniques in this study are questionnaires (questionnaire sheets), interviews, documentation, and observations. The results obtained from this research show that the effectiveness of learning physics from the homes of class X MIA students at SMA Muhammadiyah Ende during the corona virus period is categorized as quite effective, with the percentage gain for each indicator, namely for the first indicator, the percentage is 70%. with an effective category, the second indicator has a percentage of 56% with a moderately effective category, the third indicator has a percentage of 60% with a moderately effective category, the fourth indicator has a percentage of 58% with a moderately effective category, the fifth indicator has a percentage of 65% with an effective category, and the sixth indicator has a percentage of 58% with quite effective category. The average percentage gain of the five indicators is 61%. This shows that the effectiveness of learning physics from the homes of class X MIA students at SMA Muhammadiyah Ende during the corona virus period is categorized as effective, but there are some that are quite effective.